Early Menopause May Associate With a Higher Risk of CKD and All-Cause Mortality in Postmenopausal Women: An Analysis of NHANES, 1999–2014 - Qian, Duo; Wang, Zu-feng; Cheng, Yi-chun; Luo, Ran; Ge, Shu-Wang; Xu, Gang (Frontiers in Medicine, 2022)
Background: Chronic kidney disease (CKD) in women is often accompanied by hormone disorders such as sex hormones, and most women with CKD are in the post-menopausal age group. Due to the close relationship between menopause and sex hormones, we aimed to explore the association between early menopause and CKD in post-menopausal women, and the influence of early menopause on longevity in the CKD population. Methods: Information regarding 4945 post-menopausal women was extracted from the database of the National Health and Nutrition Examination Survey (NHANES) 1999-2014, and then divided into 4 groups according to the type of menopause (natural or surgical) and early menopause (menopause at age <45) or not. The association between early menopause and CKD prevalence was examined using multivariable logistic regression, while we used multivariable Cox proportional hazards models to investigate the possible relationship between early menopause and all-cause mortality in CKD and non-CKD populations. The differences in the levels of sex hormones between women with and without CKD were also explored. Results: Compared with women with natural menopause at age >=45, women experiencing early natural menopause had a higher risk of CKD (OR=1.26[1.01-1.56]). Similarly, as compared to women with surgical menopause at age >=45, women in the early surgical menopause group were more likely to have CKD (OR=1.38[1.05-1.81]). In addition, early surgical menopause was associated with higher mortality in the non-CKD group (HR=1.62[1.06-2.49]), but not in the CKD group. Women with CKD had a higher level of luteinizing hormone and follicle-stimulating hormone, combined with a lower level of testosterone and estradiol than the non-CKD women. Conclusion: Both early natural and surgical menopause were associated with a higher risk of CKD. Early surgical menopause was a hazard factor for survival in the non-CKD group, but not in the CKD group. Further research is required to understand the mechanisms.